2019
DOI: 10.1016/j.conbuildmat.2018.11.201
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of setting time and compressive strength of ready-mixed concrete blended with returned fresh concrete

Abstract: The Center for Sustainable Transportation Infrastructure (CSTI), in its 2012 study, estimated that out of all the concrete leaving the plant, between 2% and 7% of concrete returns to the plant unused as a returned fresh concrete (RFC). Disposal of both the truck wash water and RFC is a growing concern for the industry. Most industry personnel contacted during the investigation, agree that reusing is superior to recycling of this substantial RFC economically and environmentally. This study will determine if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
(2 reference statements)
1
6
0
Order By: Relevance
“…This accounts for huge amounts of waste as the annual global consumption of concrete exceeds 10 billion tons [10]. The returned fresh concrete has several possible uses, including immediate recycling or use as a source for recycled concrete aggregates [11][12][13], however, the material adhered to the inside of the barrel is washed and stored in sedimentation tanks, as it has high alkalinity [14]. The alkaline water from the sedimentation tanks finds some use replacing fresh water in concrete production [15][16][17] and the remaining material, named cement waste slurry or cement sludge fines (CSF) finds little or no use.Both MSF and CSF consist of fine particles and are produced in wet condition, which makes handling and processing more difficult, since some processing is usually required prior to transportation or use [18].…”
mentioning
confidence: 99%
“…This accounts for huge amounts of waste as the annual global consumption of concrete exceeds 10 billion tons [10]. The returned fresh concrete has several possible uses, including immediate recycling or use as a source for recycled concrete aggregates [11][12][13], however, the material adhered to the inside of the barrel is washed and stored in sedimentation tanks, as it has high alkalinity [14]. The alkaline water from the sedimentation tanks finds some use replacing fresh water in concrete production [15][16][17] and the remaining material, named cement waste slurry or cement sludge fines (CSF) finds little or no use.Both MSF and CSF consist of fine particles and are produced in wet condition, which makes handling and processing more difficult, since some processing is usually required prior to transportation or use [18].…”
mentioning
confidence: 99%
“…Bad mixing has bad effects on the mechanical properties of mortars. Ready mixed concrete has waste between 1% and 13% [25]. Part of this waste comes from job sites due to bad mixing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For reusing waste concrete when it is still fresh, hydration reactions of the cement present in the waste that returns to the RMC plant are delayed for a few hours or even for a few days by adding special chemical products, called hydrationstabilizing admixtures (HSA). Gebremichael et al [10] demonstrated the possibility of adding the HSA to stop the hydration of the concrete and allow its reuse. They also indicated that in some cases using HSA-stabilized concrete as a raw material for new concrete may increase the compressive strength of the final product.…”
Section: Introductionmentioning
confidence: 99%